Community violence exposure correlates with smaller gray matter volume and lower IQ in urban adolescents. Issue 5 (15th February 2018) - Butler, Oisin; Yang, Xiao‐Fei; Laube, Corinna; Kühn, Simone; Immordino‐Yang, Mary Helen
Abstract: Adolescents' exposure to community violence is a significant public health issue in urban settings and has been associated with poorer cognitive performance and increased risk for psychiatric illnesses, including PTSD. However, no study to date has investigated the neural correlates of community violence exposure in adolescents. Sixty‐five healthy adolescents (age = 14–18 years; 36 females, 29 males) from moderate‐ to high‐crime neighborhoods in Los Angeles reported their violence exposure, parents' education level, and free/reduced school lunch status (socio‐economic status, SES), and underwent structural neuroimaging and intelligence testing. Violence exposure negatively correlated with measures of SES, IQ, and gray matter volume. Above and beyond the effect of SES, violence exposure negatively correlated with IQ and with gray matter volume in the left inferior frontal gyrus and anterior cingulate cortex, regions involved in high‐level cognitive functions and autonomic modulation, and previously shown to be reduced in PTSD and combat‐exposed military populations. The current results provide first evidence that frontal brain regions involved in cognition and affect appear to be selectively affected by exposure to community violence, even in healthy nondelinquent adolescents who are not the direct victims or perpetrators of violence.